The Work Ethic of The Coastal Community of Java Island in The Perspective of Islamic Theology - Udin Kamiluddin; Yayat Suryatna; Muhammad Ikhsan Ghofur (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
This study examines the typology of the work ethic of the people on the North Coast (PANTURA) of Java Island and the correlation between work ethic typology and economic conditions. The research uses qualitative and quantitative methods to focus on communities in Indramayu, Cirebon City, and Cirebon Regency. Results show that 86% of respondents follow the Qadariyah Theological Doctrine, 6.6% adhere to the Jabariyah Doctrine, and another 6.6% have a combined Qadariyah-Jabariyah typology. 86% of workers in the private sector align with Qadariyah, while all civil servants follow Qadariyah. A significant correlation exists between work ethic typology and income: Qadariyah adherents generally have higher monthly incomes than those following Jabariyah or combined typologies. Respondents with Jabariyah and combined typologies typically earn less than 5 million monthly rupiah. Among the 26 respondents with a Qadariyah work ethic, 14 earn more than 5 million rupiah monthly. The study concludes that theological doctrines significantly influence work ethic and economic conditions in Java's coastal areas.